2018
DOI: 10.21125/edulearn.2018.0914
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian Educational System: In the Pursuit of Right Physical Environment for Learning

Abstract: The right physical environment of learning is a sine qua non for the realization of positive outcomes in any country's educational programme. Right environment in this work will include the combination of physical structures, right timing of teaching and learning, seating arrangement, level of sanitation and pollution of the environment, climate conditions within the environment and closeness of the learning environment to varied noise effects. According to Nigeria's National policy on education, one of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…However, no significant relationship was found between the type of school and the reading comprehension scores of the participants. This finding supports the findings of Nazir and Matto (2012) and Ngene, Quadri, Bamigboye and Tenebe (2018). These researchers found that the school social environment was directly related to academic achievement and that a positive social environment played an important role in developing students' academic abilities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, no significant relationship was found between the type of school and the reading comprehension scores of the participants. This finding supports the findings of Nazir and Matto (2012) and Ngene, Quadri, Bamigboye and Tenebe (2018). These researchers found that the school social environment was directly related to academic achievement and that a positive social environment played an important role in developing students' academic abilities.…”
Section: Discussionsupporting
confidence: 90%
“…Similar studies on learning environment in a school system and school success indicated that school environment has a significant impact on student learning (Chepkonga, 2017;Chikezie & Ekott, 2019;Duruji, Azuh & Oviasogie, 2014;Ngene, Quadri, Bamigboye & Tenebe, 2018). In addition, Michalak (2014) found that a school environment that is safe and supportive, where student motivation and classroom diversity are promoted is among the factors that facilitate literacy learning.…”
Section: Corresponding Author: Ali Dincermentioning
confidence: 93%
“…In many countries of the world, development is often a qualitative measure of the literacy rate, the productive capacity of skilled labour, level of technology, education and so on. Ngene et al (2018) stated that the educational *Corresponding author. E-mail: mnzuma1@gmail.com.…”
Section: Introductionmentioning
confidence: 99%
“…This right is recognized by the international human rights conventions as established by a succession of UN Conventions, from the Universal Declaration of Human Rights (1948) to the Convention on the Rights of the Child (1989), which acquired the status of international law in 1990. It was clearly stated in Article 28 of the Convention that governments have the responsibility of making primary education compulsory and available free to all (Ngene, Quadri, Bamigboye & Tenebe, 2018).…”
mentioning
confidence: 99%